Extent of Knowledge of Trained and Untrained Dairy Farmers of Malwa Region of Punjab - Singh, P.; Rampal, V. K. (International Journal of Bio-resource and Stress Management, 2016)
The adoption of scientific practices can be accelerated if the farmers possess scientific knowledge about the sound management practices of dairy enterprise. Dairy farming provides substantial employment opportunities and supplementary income to rural farmers. A study was conducted in the Malwa region comprising of Bathinda, Mansa and Muktsar Districts of Punjab (India) on a sample of 120 respondents i.e., 60 trained and 60 untrained dairy farmers. The ex post facto design research design was used. In order to measure the knowledge level of the trained and untrained dairy farmers, a number of items were prepared in the knowledge test with respect to improved dairy management practices in four major areas of breeding, feeding, health care and miscellaneous management. The knowledge index was calculated to see the extent of knowledge level in different aspects of improved dairy management practices (IDMPs). The investigation revealed that extent of knowledge of the trained dairy farmers was above average whereas; extent of knowledge of untrained dairy farmers was below average. The maximum knowledge index of trained farmers was 72.50 in breeding aspect and in case of untrained dairy farmers the maximum knowledge index was 49.00 in miscellaneous management. The comparative analysis indicated that there was significant difference in the mean knowledge score of different management practices at (p=0.01) level of probability of trained and untrained dairy farmers.